2017
DOI: 10.1037/neu0000318
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging the test effect to improve maintenance of the gains achieved through cognitive rehabilitation.

Abstract: Objective An important aspect of the rehabilitation of cognitive and linguistic function subsequent to brain injury is the maintenance of learning beyond the time of initial treatment. Such maintenance is often not satisfactorily achieved. Additional practice, or overtraining, may play a key role in long-term maintenance. In particular, the literature on learning in cognitively intact persons has suggested that it is testing, and not studying, that contributes to maintenance of learning. The present study inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 53 publications
1
11
0
Order By: Relevance
“…In contrast, on the basis of recent clinical work showing reliable backward testing effects in memory-impaired patient groups, one may expect the backward testing effect to be also present in patients with stroke. Reliable backward testing effects have been demonstrated in patients with Alzheimer’s disease, MS and severe TBI ( Sumowski et al, 2010a , b ; Small, 2012 ; Pastötter et al, 2013 ), and, with regard to semantic memory impairment, have also been shown in patients with stroke and chronic aphasia ( Middleton et al, 2015 ; Friedman et al, 2017 ). On the basis of these finding and the present results, a dissociation between the backward testing effect and the interference reduction effect in patients with stroke may be expected, which would point to partially different mechanisms mediating the two effects.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, on the basis of recent clinical work showing reliable backward testing effects in memory-impaired patient groups, one may expect the backward testing effect to be also present in patients with stroke. Reliable backward testing effects have been demonstrated in patients with Alzheimer’s disease, MS and severe TBI ( Sumowski et al, 2010a , b ; Small, 2012 ; Pastötter et al, 2013 ), and, with regard to semantic memory impairment, have also been shown in patients with stroke and chronic aphasia ( Middleton et al, 2015 ; Friedman et al, 2017 ). On the basis of these finding and the present results, a dissociation between the backward testing effect and the interference reduction effect in patients with stroke may be expected, which would point to partially different mechanisms mediating the two effects.…”
Section: Discussionmentioning
confidence: 99%
“…Picture naming and word to picture matching were the strategies most used (46) . Most studies used picture naming, and tablets and computers were frequently used, especially for the purpose of presenting the stimuli (13,25,26,32,37,40,47) . To improve word retrieval, some studies used progressive cueing (16,17,20,21,26,35,37,43) as it appears in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…M o s t s t u d i e s u s e d l e x i c a l -p h o n o l o g i c a l stimuli (16)(17)(18)20,22,23,(26)(27)(28)(29)33,35,40,41,43,44) and semantic stimuli (13,15,25,30,31,36,38,39,42) , and some studies used verbs (19,21,24,32,37) . Another study also reported picture naming as the main task used during word retrieval treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Fourteen out of 21 participants were tested on Exemplar set 1 before Exemplar set 2 (each set was tested in a different session). Thus, the first testing session provided an opportunity for retrieval practice (Friedman, Sullivan, Snider, Luta, & Jones, in press; Middleton, Schwartz, Rawson, & Garvey, 2015; Roediger & Butler, 2011). This opportunity followed a seven-month period during which testing of these items did not occur.…”
Section: Discussionmentioning
confidence: 99%